Integrating Islamic Literacy Values through the BAHRAIN Reading Method: A Differentiated Learning Approach in Folklore Instruction at an Islamic Elementary School - Fadhilatul Amalia Bahraini Bahar; Muhammad Guntur (Postgraduate Program of the State Islamic Institute of Palopo, 2025)
Reading literacy plays a crucial role in elementary education, yet literacy instruction often faces challenges related to learner diversity and limited opportunities for meaningful value-oriented learning. In Islamic elementary schools, literacy education is expected not only to develop reading comprehension but also to facilitate the internalization of values that support students’ character formation. This study aimed to develop and evaluate the BAHRAIN Method, a differentiated reading instruction model designed for folklore learning in an Islamic elementary school context. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research was conducted at SDIT Al-Bashirah Palopo and involved 15 fifth-grade students. Data were collected through interviews, questionnaires, validation sheets, and achievement tests, and were analyzed using descriptive qualitative and quantitative techniques. The development process resulted in the BAHRAIN Method, which consists of seven instructional stages: Baca (Read), Analisis (Analyze), Hubungkan (Connect), Refleksi (Reflect), Aktualisasi (Actualize), Interaksi (Interact), and Nilai (Value). The validation results indicated that the developed method was valid, with an overall score of 78.73%. Practicality testing demonstrated highly positive responses from teachers (100%) and students (83.5%). The effectiveness test yielded an overall score of 80.53%, categorized as effective. These findings indicate that the BAHRAIN Method is a feasible instructional model for folklore learning and has the potential to support reading comprehension, reflective learning, and the integration of Islamic literacy values within elementary literacy education. The study contributes to the development of differentiated literacy instruction by integrating cognitive, social, and value-oriented dimensions within a single instructional framework.